Default acceptance and ego-depletion: The moderating role of individual versus dyadic decision making - Grösch, Michaela; Steul-Fischer, Martina (2020)

Defaults and advice in self-customization procedures of insurance - Grösch, Michaela; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2017)

Der Einfluss von Defaults auf das Konsumentenverhalten: Experimentelle Studien zu Versicherungsentscheidungen - Grösch, Michaela (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)

Integration der Verlustangst von Kunden in den Verkaufsprozess - Steul-Fischer, Martina; Kreitmair, Michaela; Schmidt-Gallas, Dirk (Versicherungswirtschaft, 2014)

Less is more: How the number of insurance options influences customers’ default acceptance - Grösch, Michaela; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2018)

The Effect of Option Framing in Self-Other Decision Making - Grösch, Michaela; Steul-Fischer, Martina (Marketing - Forschung und Praxis - Journal of Research and Management, 2019)

The Effect of Option Framing on Consumer Choice for Service Options - Kreitmair, Michaela; Steul-Fischer, Martina (AP - Asia Pacific Advances in Consumer Research, 2015)

The impact of product variety on customers' default acceptance and company perception. Experimental studies for the insurance industry - Grösch, Michaela (Zeitschrift für die gesamte Versicherungswissenschaft, 2020)
Many insurance companies offer a huge variety of products within one insurance category. In particular, there are rarely limits to available insurance products in the online world. Insur- ance companies can simply combine various insurance sums and service components to meet the needs of different customers. Using experimental studies, the paper analyzes the effect of defaults on customer choices and customers' perceptions of the company when insurance companies offer more or less variety. The results show that defaults have an influence when a smaller, rather than a larger, number of insurance options is available. The premium image of an insurance company can only be influenced by defaults when customers know about the different default settings.<br
Keywords: Default - Variety - Behavioral economics - Choice - Decision-making - Purchase behavior